2009
DOI: 10.1161/circulationaha.108.830299
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antihypertensive Medications and Cardiovascular Morbidity Among Newly Diagnosed Hypertensive Patients

Abstract: Background-Nonadherence to antihypertensive treatment is a common problem in cardiovascular prevention and may influence prognosis. We explored predictors of adherence to antihypertensive treatment and the association of adherence with acute cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
406
3
34

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(473 citation statements)
references
References 44 publications
30
406
3
34
Order By: Relevance
“…In our study, around 60% of beneficiaries had PDC ≥80%, which is consistent with previous studies 9, 19. However, in this analysis, we observed a greater risk reduction associated with antihypertensive adherence than in other studies 13, 19, 42. In addition, our dose‐response analysis of PDC and risk for CVD events suggested a threshold effect of PDC at around 80%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, around 60% of beneficiaries had PDC ≥80%, which is consistent with previous studies 9, 19. However, in this analysis, we observed a greater risk reduction associated with antihypertensive adherence than in other studies 13, 19, 42. In addition, our dose‐response analysis of PDC and risk for CVD events suggested a threshold effect of PDC at around 80%.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our dose‐response analysis of PDC and risk for CVD events suggested a threshold effect of PDC at around 80%. Some studies also reported insignificant risk reduction comparing the intermediate adherence (40–79%) to low adherence (<40%),13, 19, 38 but others reported more‐gradual risk reduction associated with increased adherence 39, 40, 41. The reasons for the discrepancies in risk reduction are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that nonadherence to pharmacological therapy is the pivotal challenge of successful blood pressure (BP) control because antihypertensive therapy implies, in most cases, a lifelong treatment 1, 2, 3, 4. Several outcome research studies found that nonadherence to antihypertensive agents significantly increased cardiac and cerebrovascular risk 5, 6, 7. Furthermore, the choice of prescribed drug class affects adherence rates of antihypertensive therapies 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the main lifestyle modification associated with newly diagnosed hypertensive patients was smoking cessation, with an 18.6 % relative risk reduction (Neutel et al 2008). Mazzaglia et al (2009) assessed the proportion of days covered by medication in 18,806 patients (mean age, 62 years; 41.6 % were males and 27.5 % had at least one cardiovascular risk factor) at baseline, which was 6 months after newly diagnosed hypertension. At baseline, 51.4 % showed low adherence, 40.5 % intermediate adherence, and 8.1 % high adherence.…”
Section: Thrombophilia/factor V Leidenmentioning
confidence: 99%